2022
DOI: 10.3389/fimmu.2022.930979
|View full text |Cite
|
Sign up to set email alerts
|

Mast cells and tryptase are linked to itch and disease severity in mycosis fungoides: Results of a pilot study

Abstract: IntroductionIn mycosis fungoides (MF), the most common cutaneous T-cell lymphoma, itch is a frequent clinical symptom. Whether mast cells (MCs), eosinophils (Eos) or their mediators play a role in MF-associated itch or disease severity is controversially discussed. Here, we explored the role of MC and Eo numbers in the skin as well as blood levels of their mediators in disease severity and itch.MethodsIn 10 patients with MF and 10 matched control subjects we assessed disease severity, itch, and quality of life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…In a study, disease severity scores on the mSWAT scale were significantly higher in MF patients who experienced itching, indicating a more severe condition 23 . In our study, the mSWAT score was significantly higher in MS patients with pruritus compared to those without pruritus.…”
Section: Discussionsupporting
confidence: 51%
“…In a study, disease severity scores on the mSWAT scale were significantly higher in MF patients who experienced itching, indicating a more severe condition 23 . In our study, the mSWAT score was significantly higher in MS patients with pruritus compared to those without pruritus.…”
Section: Discussionsupporting
confidence: 51%
“…Tryptase induces pruritus via a PAR‐2 activated pathway, which was confirmed by inhibition of tryptase‐induced scratch behavior in mice using PAR‐2 antibodies or a PAR‐2 antagonist 114 . Clinically, the link between pruritus severity and serum tryptase was established in mycosis fungoides 115 . Several tryptase inhibitors were evaluated in early clinical trials for allergy, asthma, colitis, and psoriasis; but none of them were approved for clinical use 116 .…”
Section: Mechanisms Of Pruritusmentioning
confidence: 99%
“… 114 Clinically, the link between pruritus severity and serum tryptase was established in mycosis fungoides. 115 Several tryptase inhibitors were evaluated in early clinical trials for allergy, asthma, colitis, and psoriasis; but none of them were approved for clinical use. 116 Nafamostat, a serine protease inhibitor and potential tryptase inhibitor used for anticoagulation and the treatment of pancreatitis, had efficacy in addressing pruritus in NC mice, which mimics atopic dermatitis.…”
Section: Mechanisms Of Pruritusmentioning
confidence: 99%
“…However, although there is strong evidence in support of a direct connection between tryptase and itch from various diseases, there is currently only one study that involved a small group of patients with MF. This study observed numerically higher serum levels of tryptase in MF patients with pruritus compared to those without pruritus [ 204 ]. Furthermore, since tryptase is a marker of mast cell activation, any association between pruritus and tryptase may reflect the role of mast cell activation and the consecutive release of other pruritus associated mediators.…”
Section: Proteasesmentioning
confidence: 99%